Corn and grain sorghum response to limited irrigation, drought, and hail - Klocke, Norman L.; Currie, Randall S.; Kisekka, Isaya; Stone, Loyd R. (My University, 2014)
A field study was conducted for eight years in southwest Kansas near Garden City to measure the response of corn and grain sorghum to limited irrigation in the region. An irrigation variable was imposed on each crop, with six irrigation treatments from full irrigation scheduled to minimize soil water deficits to minimal or no irrigation. To create differences in the amount of irrigation across treatments, the time between 25-mm irrigation events increased as irrigation decreased. A historic drought occurred during 2011 and 2012 when cropping season precipitation, the precipitation occurring from the harvest of the prior crop through the harvest of the next crop, was 60% of the 30-year average. Except for 2008, average cropping season precipitation was 8% above average during the prior six years. Linear regressions of corn and sorghum grain yields (GY) and dry matter yields (DMY) versus crop evapotranspiration (ETc) from all years combined, except hail damaged sorghum in 2005, produced R2 values from 0.71 to 0.79. One hailstorm during 2005 damaged sorghum to the extent that yields did not vary with respect to ETc or irrigation. Hail events in 2005 and 2006 occurred at nearly the same growth stage for corn caused lower leaf area and yields than during other wet years with no hail. Using quadratic regressions, corn yields during wet years with no hail, wet years with hail, and dry years had distinctly different dependence on irrigation. Although sorghum yields during wet years tended to increase as irrigation increased, sorghum’s response to irrigation was less than for corn during the same years. During dry years, sorghum and corn were highly dependent on irrigation. Net economic returns (NR) of continuous corn, continuous sorghum, cornsorghum, corn-wheat, and sorghum-wheat rotations were each higher with a year receiving average precipitation (460 mm) than a year receiving 60% of average precipitation (280 mm). The NR of continuous corn dominated the rest of the rotations when irrigation was more than 230 to 330 mm in the dry year and 90 to 180 mm in wet year. As farmers choose crop rotations, they need to consider management factors and crop tolerance to soil water stress in addition to potential NR.
Keywords: Corn; Crop production functions; Deficit irrigation; Irrigation; Irrigation management; Sorghum; Wheat; Limited irrigation